Preparations and Properties of Porous Copper Materials for Lithium-Ion Battery Applications. Issue 6 (2nd June 2016) - Liu, Lehao; Lyu, Jing; Zhao, Tingkai; Li, Tiehu
Abstract : Because of its special porous structure and novel physical and mechanical properties, porous copper is widely studied in many fields, especially in high-performance lithium-ion batteries. It is quite necessary for researchers to understand the recent progress of porous copper. Herein, we review the preparations, properties, and lithium-ion battery (LIB) applications of porous copper. Its main research direction and development trend are also pointed.